A case–control study of occupational risk factors for pancreatic cancer in poultry plant workers: a random forest approach. (25th February 2021) - Faramawi, Mohammed F; Abouelenein, Saly; Johnson, Eric
Abstract: Background: Poultry plant workers are exposed to chemical carcinogens and oncogenic viruses in their work environment. Our objective was to identify jobs and workplaces related to poultries that could increase the pancreatic cancer risk. Methods: We conducted a case–control study within a defined cohort of poultry workers. We used a random forest algorithm to identify features that could increase pancreatic cancer in the poultry plant workers. Results: The mean age of participants was 59.49 years. The majority of the study participants were females (51.30%) and Whites (71.0%). The following workplaces and job tasks had an association with increased pancreatic cancer mortality: working in chicken and turkey plants, working in plants where food products were processed and canned, working in a place where poultry and animals where present, working as a hunter for game animals, working as a veterinarian in places had animals and different poultry birds, working in pet houses and working in places where birds were handled and killed. The accuracy and the area under the curve of the model were 72.3 and 71.50%. Conclusion: Chicken and turkey plant workers could be at risk for pancreatic cancer mortality. We need to confirm the results in future studies.